Easy-to-read Polish. Considerations on a new linguistic phenomenon - Radünzel, Claudia (Glottodidactica, 2020)
The present article deals with Easy-to-read Polish, a language variety which has been created for target groups with difficulties in reading and understanding written standard text. It is systematically simplified in both syntax and vocabulary. In order to describe Easy-to-read Polish, this article consults findings made in the last few years in examinations of Easy-to-read German. The analysis is based on texts in Easy-to-read Polish which were published by the organization “Inclusion Europe” on their homepage. With the help of these texts, characteristic features of the Easy-to-read language on various linguistic levels such as the system of symbols, morphology, syntax, vocabulary, semantics, and text are being worked out and illustrated by examples. It turns out that findings on Easy-to-read German are definitely helpful and inspiring for the elaboration of this language variety in Polish. Yet, in many cases more detailed language specific research is required.